POTENSI Salmonella typhi YANG DILEMAHKAN DENGAN SINAR ULTRAVIOLET SEBAGAI VAKSIN ALTERNATIF - Santoso, Andreas Putro Ragil; Kawuri, Retno; Besung, I Nengah Kerta (Metamorfosa: Journal of Biological Sciences, 2016)
Salmonella typhi is a Gram-negative intracellular bacterium and causes typhoid fever in humans. The success rate of Berma Vivotif Ty21a vaccine in Indonesia is only 33-66%, while in other countries have been reached up to 100%. The research was conducted in order to determine the potency of local isolate bacteria to stimulate the immune response and the impact of different exposure frequencies on the immune response and the different immune response time when administered by UV-inactivated vaccine.. The results showed that the antibody titer of local isolates irradiated by UV light 10x was 88.76 ± 33.06 IU/mL at week 4 with the lowest antibody titer values about 11.15 ± 9.18 IU/mL was found in the negative control.
Keywords: Salmonella typhi, Ultraviolet, Immune ResponseTime , antibody titers